Мікрорайони 60–70-х рр. ХХ ст. в оцінках і преференціях мешканців - Гнесь, І.; Бурко, Н.; Hnes, I.; Burko, N. (Видавництво Львівської політехніки, 2019)
Розглянуто питання комфортності проживання в мікрорайонах, збудованих у 60–70-х рр. ХХ ст. на рівні житлових дворів, житлових будинків та квартир. Подано результати соціологічного опитування мешканців мікрорайонів Львова, визначено найпоширеніші проблеми проживання в житловій забудові 60–80-х рр. та наведено рекомендації щодо вирішення в послідовності їх актуальності для мешканців.

It is considered living conditions, including yards, residential houses and flats, in morally outdated city districts whichwereconstructed in the 1960s-70s.There are results of the survey which was carried out online and with personal interviewing of the residents of the districts in June 2019 in Lviv, Ivano-Frankivsk and Kolomyia.The most widespread problems of the districtshave been identified as well asthe recommendations on their solving have been made in accordance with their importance. The high quality of living environment of the districts constructed in the 1960s-70shas been confirmed by the residents which excludes any options of demolition of the existing buildings for the purpose of construction a completely new housing at the same place but which requires the development of design for reconstruction.Priority towards improving living conditions mainly relates to overhaul of internal engineering networks and some structural parts of the buildings as well as transport and pedestrian infrastructure of the neighborhoods.Among the shortcomings there is lack of privacy of the areaaround the buildings, its accessibility to the strangers, lack of recreation for children and adults, poor housing architecture and its uniformity.There is a significant need for underground parking facilities. Except for the poor state of engineering, roofs, front doors, staircasesof the residential houses require complete overhaul.Also it is considered asa disadvantagethe lack of storage space for bicycles orpushchairs and the need for children’s rooms.The best option can be building up attics in the existing houses, where comfortable apartments which are not functionally connected to the lower floorshouldbe accommodated.For 60 % of people the elevator in their residential building is an asset which allows them to tolerate flaws of six and higher floor buildings while only 23 % of the respondents would agree to have an apartment higher thanthe eighth floor. For 30 % of residents, the benefits of a medium-height dwelling are more important than having an elevator. Considering thevery apartments the major drawbacksarepoor sound insulation of the rooms from internal or external noise and too smallsizesof kitchens, bathrooms andstorerooms.The respondents suggest the solving of the issues as rearrangement of the apartment layout under renovation, as well as uniting of neighbouring apartments. The residents who live on the first floor and upper floors would like to have a terrace attached to their apartment, while the ground-floor residents would like to use the area outside their apartment as a private patio or consider it as a potential opportunity for extension by adjoining a winter garden, a veranda, a storeroom or some living space to their apartment.In case of necessaty to attach a new building to the wall of the existing house the most desirable compensation for the loss of windows for the residents could be either an additional room of 10–15 m² or moving to a new apartment.About 15 % of residents will oppose any renovation if their apartments are involved directly. On the whole, the residents’ vision of the main directions for improving of living conditions in residential districts corresponds to the tendencies of modern urban housing development and does not set any impossible tasks fordesigners and potential investors.
The 1960s–70s city districts in evaluations and preferences of the residents
Keywords: житло; панельні будинки; “хрущовки”; реконструкція житла; стан інженерних мереж; гаражі; термін експлуатації будівель; housing; panel houses; “Khrushchev”; housing reconstruction; state of engineering networks; garages; life of buildings; 711.728.31